Raven Halfmoon - flags of our mothers - Smith-Stewart, Amy; Adams, Rachel; Drake, Kinsale (Gregory R. Miller & Co, 2023)
"Born and raised in Norman, Oklahoma, Raven Halfmoon (born 1991) learned traditional ceramic techniques as a teenager from a Caddo elder. Her celebrated practice spans torso-scaled to colossal stoneware sculptures, with some soaring up to nine feet and weighing over 1,000 pounds. These dramatic totemic works reference stories of the Caddo, the feminist lineage of indigenous artmaking and the complexities of her lived experience. Produced in conjunction with the exhibition of the same name, co-organized by The Aldrich Contemporary Art Museum and Bemis Center for Contemporary Arts, Flags of Our Mothers presents work made over the last five years, including some of the artist's largest sculptures to date. Fully illustrated with texts by the co-curators and a new commissioned poem by Kinsale Drake, this publication marks Halfmoon's first museum catalog." --
Impressum: Published on the occasion of the exhibition "Raven Halfmoon: Flags of Our Mothers" ... The Aldrich: June 25, 2023 to January 7, 2024; Bemis Center: May 18, 2024 to September 15
Keywords: Raven Halfmoon -- 1991-; Geschichte 2019-2022; Plastik; Steinzeug; Indianer; Ausstellungskatalog -- Aldrich Contemporary Art Museum -- 25.06.2023-07.01.2024 -- Ridgefield, Conn.; Ausstellungskatalog -- Bemis Center for Contemporary Arts -- 18.05.2024-15.09.2024 -- Omaha, Neb.